(untitled) (Fiep Bulletin - online, 2014)
This study aimed to identify the profile of six-year-old Municipal school’s students of Ipatinga, MG, regarding their promptitude level for literacy. 1.073 six- year-old female and male students of Municipal school took part in this study. “Promptitude Metropolitan R-Type Test” (TMP) by HILDRET & GRIFFITHS was used to evaluate the students’ promptitude for literacy, adapted and standardized by Poppovic (1966). This test is subdivided in six other ones: word, sentence, information, similarity, numbers and copy and a supplementary test “draw a man”. The TMP aims to analyze the vocabulary, the capacity of concentrated attention, listening and visual perception, the visual-motor correction, movement coordination, tendency to inversion and the elements which are necessary to arithmetic learning. The evaluation was done in teams, in the students own classrooms during their regular school schedule, by following all the application instructions, according to the TMP application manual. With the obtained results it was concluded that, 40% of six-year-old students of municipal schools in Ipatinga are classified as “inferior” and medium inferior regarding their promptitude for literacy. These results show that, such students need to have better support with language activities, games, body experiences through flurry activities, to improve their non-verbal skills through psychomotor stimulation in order to reach properly promptitude for literacy. 37, 2% of the students are classified as “medium”, that means their development won’t probably face losses or restrictions in the process of literacy since they’re duly stimulated under a properly planning. 22,5% of the students were classified as “medium-superior” and “superior”. They will probably have great chances in the process of literacy since counter-indications such as health, emotional factors etc, do not exist.